Staging negotiation spaces: A co-design framework. (May 2020) - Pedersen, Signe
Abstract : Today, many design projects are collaborative in nature. This means that designers must navigate multiple concerns held by a range of involved actors. This article investigates the expansion of the designer role from creative expert to stager and facilitator of negotiations during the design process. In doing so, the metaphorical notion of an inviting stage director is used to develop a new framework termed 'staging negotiation spaces'. This framework is informed by experiences and practices from participatory design and analytical insights from actor-network theory. To illustrate the applicability of the framework, it is used to analyse and understand the staging, facilitation, and reframing of negotiations during a co-design process in a large international electronics company. Highlights: Identifies gap in research related to how designers stage and navigate negotiations. Presents a case study which highlights the role of designers as strategic navigators. Staging involves configuring spaces with changing actors, object and frames. Conceptualizes and introduces a framework termed staging negotiation spaces . Staging negotiation spaces is suggested as a sensitising device for practitioners.